Respuesta :

The answer to your question is h=−4

Answer:

[tex]h=-4[/tex]

Step-by-step explanation:

The equation is [tex]-3(h+5)+2=4(h+6)-9[/tex] we need to find the value of h.

First we are going to distribute the products.

[tex]-3(h+5)+2=4(h+6)-9\\ -3h-15+2=4h+24-9\\ -3h-13=4h+15[/tex]

We have to put the terms with letter h in the left side of the equation and the terms without h in the right side;

[tex]-3h-13=4h+15\\ -3h-4h=15+13[/tex]

[tex]-7h=28[/tex]

Now, for the last step we have to divide both sides of the equation in (-7):

[tex]-7h=28\\ \frac{(-7)h}{(-7)} =\frac{28}{(-7)} \\ h=-4[/tex]

ACCESS MORE